Deteksi Kandungan Hg, Cd, Pb di Tulang Sirip Keras Ikan Sembilang (Plotosus canius Web & Bia) di Muara Sungai Kahayan dan Katingan / Detection of Hg, Cd, Pb Content in Catfish Hard Fin Bone (Plotosus canius Web & Bia) in the Estuary Kahayan and Katingan - Edison Harteman (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
Mining, logging and forest fires along the stream Kahayan and Katingan in Central Kalimantan effected of Hg, Cd and Pb in river and estuarine waters rise. The aim of this study was to evaluate the content of Hg, Cd and Pb in the hardfin bone of Catfish in estuaries. Samplings were done once a month and three replicates per station for four months. Extracts of Hg, Cd and Pb were contained within the hardfin bone tissue of Catfish were analyzed using Atomic absorption Spectrophotometer. The results showed that all catfish hardfin bone samples in the estuary Kahayan containing an average of 0.018 mgHg/kg, 0.029 mgCd/kg and 0.944 mgPb/kg; hardfin bone tissue of Catfish in the estuary Katingan river containing an average of 0.021 mgHg/kg, 0.027 mgCd/kg and 0.802 mgPb/kg. Hardfin bone of Catfish had the capacity to accumulate Hg higher than Cd and Pb.